PENGUATAN KARAKTER PROFIL PELAJAR PANCASILA DALAM IMPLEMENTASI P5 PADA KURIKULUM MERDEKA DI SDN 98 PEKANBARU - Fatilah Khairina; Nafisyah Rahma Salsa; Jihan Humaira; M. Jaya Adi Putra; Maiuliatun Nisa (CV. ADIBA ASIHA AMIRA, 2024)
This study examines the implementation of the Program for Strengthening the Appreciation and Practice of Pancasila (P5) in the Independent Curriculum at SDN 98 Pekanbaru. Using a descriptive qualitative approach, this study involved interviews with two grade VI teachers. The results show the success of the integration of Pancasila values through various programs for three years of implementation, with the role of teachers and the learning environment as key factors. Positive changes can be seen in student behavior, although there is still a need to develop an evaluation system and increase the involvement of parents and the community. The implementation of P5 has proven to be effective in creating a learning environment that supports the formation of student character in accordance with Pancasila values.